46 Promoting Advance Care Planning of Patients with Parkinsonism in the Community. (16th March 2021) - Lim, C Khuang; Miller, C; Jones, T
Abstract: Introduction: NICE guideline recommends that all patients with Parkinson's disease should be reviewed every 6–12 months and offered opportunities to discuss Advanced Care Planning (ACP) (1, 2). There is evidence demonstrating that Advanced Care Plans results in shorter length of stay in the last year of life and lower hospital costs (2, 3). A local baseline audit showed that Advanced Care Planning was not performed adequately. Methods: A local baseline audit on community care home patients with Parkinsonism was completed in February 2018. A community-based Parkinson's clinic was commenced in June 2018. Patients with parkinsonism who were unable to attend hospital clinics due to underlying frailty, neuropsychiatry and physical issues, were reviewed. At each visit, advice was provided on medicines management and there were discussions around Advance Care Planning. A re-audit was completed in August 2019. Patient's Electronic Patient Records were scrutinised to evaluate progress and identify those who had died. Data was analysed using Microsoft Excel. Results: The initiative contributed directly to end of life care in 7/17 patients. Parkinson's disease medications were rationalised in 11/17 (64.70%). 14/17 (82.35%) had a community-based Do Not Resuscitate order completed. Conclusions: The community Parkinson's clinic service promoted Advance Care Planning in patients with Parkinsonism. This service provides specialist input in frail older people with Parkinsonism who were unable to attend hospital clinic, promoting end of life choices around where they wished to die and avoiding unnecessary hospitalisation in the final stages of their life.